2005
DOI: 10.1093/eurheartj/ehi579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biventricular pacing on interstitial remodelling, tumor necrosis factor-α expression, and apoptotic death in failing human myocardium

Abstract: We provide the first evidence that CRT reduces interstitial remodelling, TNF-alpha expression, and apoptosis. The data may explain the beneficial effects of CRT on CHF progression and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 27 publications
9
54
0
4
Order By: Relevance
“…19 Recent data from D'Ascia et al demonstrated that myocardial tissue from patients revealed a significant decrease in TNF-␣ expression with increased capillary density after 6 months of cardiac resynchronization therapy. 36 Moreover, endotoxemia tended to decrease intestinal functional capillary density, whereas it elevated TNF-␣ and interleukin levels in rats. 37 It is suggested that an increase in capillary density is not followed by an increase in inflammatory responses.…”
Section: Et Al Effect Of Temporal Pretreatment With Arb On Stroke mentioning
confidence: 95%
“…19 Recent data from D'Ascia et al demonstrated that myocardial tissue from patients revealed a significant decrease in TNF-␣ expression with increased capillary density after 6 months of cardiac resynchronization therapy. 36 Moreover, endotoxemia tended to decrease intestinal functional capillary density, whereas it elevated TNF-␣ and interleukin levels in rats. 37 It is suggested that an increase in capillary density is not followed by an increase in inflammatory responses.…”
Section: Et Al Effect Of Temporal Pretreatment With Arb On Stroke mentioning
confidence: 95%
“…However, recent studies by our and other laboratories have revealed many changes at the cellular and molecular levels as well, and these present a unique profile for CRT unmatched by other HF treatments to date. For example, marked heterogeneity of regional gene expression is reversed (10), the cytoprotective Akt pathway is stimulated and is coupled with reduced apoptosis (11,12), calcium handling and associated ultrastructure of the sarcoplasmic reticulum improve (13)(14)(15), mitochondrial efficiency and ATP synthase activity are enhanced via a redox switch (16), ion channel function regulating the action potential is improved (17,18), and resting as well as β-adrenergicstimulated myocyte function are markedly restored by a mechanism involving regulators of G protein signaling (19,20). Interestingly, while CRT substantially improves resting myocyte function throughout the ventricle, this is not consistently matched by increases in the calcium transient (17,20), suggesting CRT may also enhance myofilament responses to calcium.…”
Section: Introductionmentioning
confidence: 99%
“…CRT is also associated with decline in global apoptosis and enhanced cell-survival signaling [60,61]. Biventricular pacing reduces interstitial remodeling [61].…”
Section: Cardiac Resynchronization Therapy (Crt)mentioning
confidence: 99%